Labour relations in the conditions of innovative development of the Russian Federation - L. N. Mordisheva; E. V. Shchanina (Цифровая социология)
The article provides information about priority directions for development of the information society in the Russian Federation. Based on the analysis of data from the Federal State Statistics Service on the indicators and costs of innovative activities of organisations for the period from 2010 to the present, the most and least active areas of innovative organisations are identified which emphasises the unevenness of innovation processes occurring in the country. The key role of investing in the innovative development of the country to ensure sustainable economic development and social stability of Russia is noted. An analysis of current trends in the labour market has recorded an increase in the importance of stability of the company in the market and type of employment as criteria for choosing an employer. A secondary analysis of research results obtained from the recruiting company Get Experts and from the research service of the Russian online recruiting platform HeadHunter made it possible to identify problems of job satisfaction in modern conditions, causes and manifestations of chronic fatigue among employees and employers, and causes of burnout in the workplace. On the basis of the findings, it was concluded that job satisfaction in the conditions of innovative development of the society depends on the extent to which employees can use new technologies and tools to improve their work, develop their skills and knowledge, and also to be involved in decision-making and the development of new ideas.